Central de monitoramento de variáveis climáticas utilizando um sistema embarcado - Sarmento, Francisco Danillo de Lima (Universidade Federal Rural do Semi-Árido, 2019)
Over the years we have come to understand the importance of the study of climatic phenomena,we become able to make predictions and perfect countless human activities through understanding the climate. In this context, it is necessary to study more and more accessible forms of climate monitoring, since most of the equipment is not yet affordable. The present work aims to demonstrate a possible way of building a monitoring center for climate variables using an embedded system through an Arduino microcontroller and some sensors it is possible to measure variables such as rainfall, relative humidity, temperature, wind speed and soil moisture. The present work also demonstrates that the data obtained through the sensors can be stored through a datalogger for future uses. The total cost of the project as well as the comparison with market models is done in order to attest its economic viability.
Central monitoring of climatic variables using an embedded system
Monografia
Keywords: Arduino®; Estação metrológica; Variáveis climáticas; Metrological station; Climatic variables; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA